Machine learning: how much does it improve the prediction of unplanned hospital admissions? - Colin Weaver; Kerry McBrien; Tolu Sajobi; Paul E Ronksley; Brendan Lethebe; Tyler Williamson (International Journal of Population Data Science, 2018)
Introduction Risk prediction models can be used to inform decision-making in clinical settings. With large and detailed electronic medical record data, machine learning may improve predictions. The objective of this work is to determine the feasibility and accuracy of machine learning versus logistic regression to predict unplanned hospital admissions.